PSYCHOSOCIAL EFFECTS OF FACEBOOK ON NURSING STUDENTS AT THE FACULTY OF NURSING, CAIRO UNIVERSITY - Amal Gamal Shehata; Enas Mahrous Abd El Aziz (Indian Journal of Psychiatric Nursing)
Facebook is the most popular online social network among youth and used by more than one billion people. The over use of Facebook on daily basis has many negative effects, so it adversely affects psychosocial wellbeing of youth. To investigate the effects of Facebook on psychosocial aspects among nursing student's descriptive exploratory design was adopted. This study was conducted at faculty of nursing, Cairo University. One hundred convenient sample of nursing students from the Faculty of Nursing, Cairo University were recruited from the users of digital library at the faculty of nursing, from level 1 up to 4 (10% from each). Intensity of Facebook Use, Short Depression-Happiness, Social Trust and, Rosenberg Self-esteem Scales were used. Findings revealed that, 70% of the entire sample had 200 contacts, 58% of Facebook users spend 1-5 hours daily. The results showed statistically significant difference between highly, medium and low users of Facebook with the depression happiness Social trust Scale, and self- esteem scales